The Prevalence of Non-Prescription Drugs and Related Factors in Students of Medical Sciences in 1392 - M Margdari Nejad; SB Kazemi; F kord; M Khosravi; A Sanagoo; L Jouybari (Iran University of Medical Sciences, 2017)
Background & Aim: The scientific advances have been caused more access to the medication. The easy accessibility as harmful social phenomena (i.e misuse of medication) is widespread problem in many countries. Self-medication is one of the greatest social and economic health problems of the country. The aim of study was to explore prevalence of self-medication practice among medical students and its relationship with some factors. Material & Methods: In this descriptive cross- sectional study using convince sampling 262 of the students were participated. The data collected by valid and reliable questionnaire consisted two parts; demographic and specific questions related to medication consumption. The data analyzed using SPSS.16 and interpreted by  Chi-Square and T-Tests. Results: 51.1 percent of the students were of male. The most commonly used drugs were analgesics 84/8% (229 cases), antihistamines 76/4% (207 people), common cold medications. The most important factor for self-treatment (67.5%) was feeling no need to visit a doctor because of mild symptoms.  The most important source for the access to the medication was the pharmacy 34/1 stores. Conclusions: The prevalence of self- medication with drugs without prescription was high. The most commonly used drugs were analgesics. The public education to increase awareness s0till seems necessary.